I wonder what Noah did with the woodpeckers : tales from the far side of Christian life - Wildmon, Tim 1963- (Promise Press, 1998)
"Can we learn to better love God and serve our fellow man by apusing to contemplate everyday events? Perhaps there are lessons in each episode of our lives--golden nuggets of truth that can be mined..."--jacket.